IOs in the BBNJ Regime Complex – the Dataset - Arne Langlet; Alice Vadrot (Data in Brief, 2023)
The dataset on the involvement of international organizations (IOs) in in the negotiations for a new legally binding instrument for the conservation and sustainable use of marine Biodiversity Beyond National Jurisdiction (BBNJ) under the United Nations Convention on the Law of the Sea (UNCLOS) underlies the visualizations (Figure 1,2,3) and overview (Table 1) in the publication “Not ‘undermining’ whom? Unpacking the emerging BBNJ regime complex”. The dataset describes the involvement of IOs in the negotiations through participation, making statements, being referred to by states, hosting side events and being mentioned in a draft text. Every involvement was traced to one of the package items of the BBNJ agreement, as well as to the specific provision of the draft text, where the involvement occurred.